A Class of Rigid Annular Disc Inclusion Problems Involving Translations and Rotations
The paper considers the class of problems related to the annular inclusions located in an elastically supported layer. The layer is considered to be transversely isotropic and the inclusion is located on the plane of symmetry. The analysis is based on the potentia